2008
DOI: 10.2137/1239099041837950
|View full text |Cite
|
Sign up to set email alerts
|

Impact dehulling oat grain to improve quality of on-farm produced feed : 2.Groat breakage and storability

Abstract: Dehulling improves markedly the feed value of oat (Avena sativa L.), but good storability of groat mass is required when large quantities of oat are dehulled at any one time. A laboratory model of an impact oat dehuller, similar to a commercial device, was used to study the effects of rotation speed and grain moisture content on groat breakage and the storage life of oat groats. Grain of oat cultivar Salo [from official variety trials, MTT Agrifood Research Finland, Jokioinen (60˚49'N), 1996-2000 was dehulled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…The protein content of oats usually varies between 10 and 20% (dm), but values as high as 25% (dm) have been reported. Peltonen-Sainio et al [24] noted that the share of protein was higher after de-hulling, with an increase from 12.7% in oat grains to 15.6% in oat groats, which aligns with the current results.…”
Section: Variation In the Properties Of The Oat Raw Materialssupporting
confidence: 91%
See 1 more Smart Citation
“…The protein content of oats usually varies between 10 and 20% (dm), but values as high as 25% (dm) have been reported. Peltonen-Sainio et al [24] noted that the share of protein was higher after de-hulling, with an increase from 12.7% in oat grains to 15.6% in oat groats, which aligns with the current results.…”
Section: Variation In the Properties Of The Oat Raw Materialssupporting
confidence: 91%
“…The variation between the chemical composition of the different oat samples (n = 30) was expected, as the composition depends on the growth conditions, location, cultivar and variety [15,24,25]. It is important to note that although all of the samples were produced and analysed as pure cultivars, the experimental design used does not reveal linkages to the role of the cultivar, location, crop year or growth conditions; instead, we focused on revealing the factors of industrially produced oat flours in relation to the properties of the native grains.…”
Section: Variation In the Properties Of The Oat Raw Materialsmentioning
confidence: 95%
“…On the other hand, grains which did not dehull at low rotation speeds tended to have lower hull content than that of the intact grains. As the energy content of groat mass is closely associated with the amount of retaining hulls, the best rotation speed is primarily a compromise between degree of dehulling and groat breakage (Peltonen-Sainio et al 2004b). This is particularly important if there is a risk of reduced storability resulting from increased groat damage.…”
Section: Discussionmentioning
confidence: 99%
“…The small grains tended to require higher rotation speeds to be released from hulls (Peltonen-Sainio et al 2004b). Thus, for example, a large number of typically small sized tertiary grains (Palagyi 1983) in the grain mass might decrease hullability and require use of greater mechanical stress to yield groats with markedly improved metabolised energy content.…”
Section: Volmentioning
confidence: 99%
“…Furthermore, conventional oat tended to produce higher amounts of hexanal than naked oat if differences occurred (Kirkkari et al 2004). An additional study by Peltonen-Sainio et al (2004b) with dehulled, conventional oat indicated that production of volatile compounds was not positively correlated with degree of grain damage. Even storage at high temperatures of up to 30˚C did not enhance rancidification processes in terms of production of volatile compounds when grains were stored under dry conditions.…”
Section: Storabilitymentioning
confidence: 92%